Intellectual Property Rights (IPR) Protection of Palembang Songket Weaving as Traditional Cultural Heritage in Indonesia - Merry Aryanti; KMS Herman (PT. ALHAFI BERKAH INDONESIA, 2025)
The Palembang songket woven fabric is one of Indonesia’s traditional crafts that holds high historical, cultural, and economic value. It is a cultural heritage with deep historical roots dating back to the era of the Palembang Darussalam Sultanate. Songket fabric is not only a symbol of textile aesthetics but also represents spiritual values and the social structure of the traditional Palembang community. With its distinctive weaving techniques and rich motifs, the philosophical meaning of songket has become an intangible cultural expression passed down through generations. However, in the era of globalization and the expansion of the modern textile industry, songket faces various challenges, including unauthorized commercial exploitation, design counterfeiting, and the degradation of cultural values. This study aims to analyze the legal protection mechanisms through Intellectual Property Rights (IPR) for Palembang songket as traditional cultural heritage. The method used is normative-juridical research, with analysis of national regulations such as Law Number 28 of 2014 on Copyright, Law Number 20 of 2016 on Trademarks and Geographical Indications, and international conventions such as the 2008 UNESCO Convention for the Safeguarding of Intangible Cultural Heritage. This study applies an IPR framework with a collective rights and cultural approach, alongside regional regulations like the South Sumatra Provincial Regulation Number 5 of 2015 on the Preservation and Development of Regional Culture. This regulation emphasizes the importance of developing a commodity-based protection system and incorporating customary law to preserve and economically empower local artisan communities. Adequate legal protection will strengthen songket's position as both a cultural identity and a sustainable economic asset. The results of this research recommend an integrative approach between positive law and culturally-based commodity empowerment to establish fair, sustainable, and contextual protection for Palembang songket woven fabric as an inseparable part of Indonesia’s cultural identity.